Diabetes and the Affordable Care Act - Burge, Mark R. (Mary Ann Liebert, Inc., 2014)
The Affordable Care Act—“Obamacare”—is the most important federal medical legislation to be enacted since Medicare. Although the goal of the Affordable Care Act is to improve healthcare coverage, access, and quality for all Americans, people with diabetes are especially poised to benefit from the comprehensive reforms included in the act. Signed into law in 2010, this massive legislation will slowly be enacted over the next 10 years. In the making for at least a decade, it will affect every person in the United States, either directly or indirectly. In this review, we discuss the major changes in healthcare that will take place in the next several years, including (1) who needs to purchase insurance on the Web-based exchange, (2) the cost to individuals and the rebates that they may expect, (3) the rules and regulations for purchasing insurance, (4) the characteristics of the different “metallic” insurance plans that are available, and (5) the states that have agreed to participate. With both tables and figures, we have tried to make the Affordable Care Act both understandable and appreciated. The goal of this comprehensive review is to highlight aspects of the Affordable Care Act that are of importance to practitioners who care for people with diabetes by discussing both the positive and the potentially negative aspects of the program as they relate to diabetes care.